Discovering the Targets of Drugs Via Computational Systems Biology - Chua, Hon Nian (American Society for Biochemistry and Molecular Biology, 2011)
Computational systems biology is empowering the study of drug action. Studies on biological effects of chemical compounds have increased in scale and accessibility, allowing integration with other large-scale experimental data types. Here, we review computational approaches for elucidating the mechanisms of both intended and undesirable effects of drugs, with the collective potential to change the nature of drug discovery and pharmacological therapy.